Update on CRISPR Research for Citrus Improvement - Wang, Nian; Gmitter, Fred; Dutt, Manjul (EDIS, 2020)
In recent years, genome editing, using a system called CRISPR (clustered regularly interspaced short palindromic repeats) has raised incredible new possibilities for citrus improvement. CRISPR is being used to make small changes in the DNA sequence of citrus trees, resulting in specifically targeted mutations. Major advances in the ability to decipher the genetic blueprint of any living organism, including citrus, have been made possible by the development of new genome-sequencing technologies and powerful computers. Many commercially important citrus types have been or are in the process of being sequenced. Peer reviewed through UF/IFAS Citrus Research and Education Center; published in Citrus Industry Magazine.